2019
DOI: 10.3892/etm.2019.7787
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of fatalities of road traffic accidents associated with alcohol consumption and the use of psychoactive drugs: A 7-year survey�(2011-2017)

Abstract: Driving under the influence of alcohol and/or psychoactive substances increases the risk of severe, even fatal motor vehicle accidents. The aim of this descriptive study was to present the impact of alcohol and/or psychoactive substances on fatal road traffic accidents (RTAs) during the period 2011-2017. For this purpose, the toxicological investigation reports from the Department of Forensic Medicine and Toxicology of the University of Athens were used. In total, 1,841 (32.2%) of the autopsies conducted by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 50 publications
2
45
0
Order By: Relevance
“…Studies on the role of ethanol in road traffic accidents indicate that ethanol is a factor that has a significant influence on their occurrence and effects. The problem of drink-driving is the most commonly discussed, although alcohol is a documented risk factor also for pedestrian accidents, and intoxicated pedestrians pose a potential risk to themselves and other road users [30,31,32,33]. Even low concentrations of ethanol cause visual-motor coordination disorders, speech impairment, delayed reaction times, problems with balance and self-control of one's behaviour.…”
Section: Risky Behaviour Under the Influence Of Ethanolmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the role of ethanol in road traffic accidents indicate that ethanol is a factor that has a significant influence on their occurrence and effects. The problem of drink-driving is the most commonly discussed, although alcohol is a documented risk factor also for pedestrian accidents, and intoxicated pedestrians pose a potential risk to themselves and other road users [30,31,32,33]. Even low concentrations of ethanol cause visual-motor coordination disorders, speech impairment, delayed reaction times, problems with balance and self-control of one's behaviour.…”
Section: Risky Behaviour Under the Influence Of Ethanolmentioning
confidence: 99%
“…Thus, the sobriety threshold is 0.19‰ and the value of 0.2‰ is an offence. At this point, it should be noted that the "intoxication" of pedestrians does not give rise to legal liability, although it also poses a serious threat to road safety [30,31,32,33].…”
Section: Risky Behaviour Under the Influence Of Ethanolmentioning
confidence: 99%
“…Among the alcohol-associated disorders, those affecting the nervous system can lead to fatal consequence such as traffic injuries [47], suicide [48,49], and interpersonal violence [50]. Furthermore, recent studies have associated alcohol abuse with many On the other hand, as clearly shown in Figure 8 (panel B), ZO-1 cellular distribution was severely altered after 1 h even at lower concentrations (50 and 75 mM) in comparison with control group where a ZO-1 continuous distribution at the cell-cell borders was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Among the alcohol-associated disorders, those affecting the nervous system can lead to fatal consequence such as traffic injuries [47], suicide [48,49], and interpersonal violence [50]. Furthermore, recent studies have associated alcohol abuse with many…”
Section: Discussionmentioning
confidence: 99%
“…Vehicle collision or car crash is one of the pervasive events putting human health at risk. Mortality due to traffic-related injuries is a public health concern in many countries, particularly in lowincome countries (1)(2)(3). According to the World Health Organizationʼs annual report, 1.24 million people (18 in every 100,000 individuals) lose their lives due to roadway crashes, and over 50 million individuals are reported with injury or disability.…”
Section: Introductionmentioning
confidence: 99%